First row transition metal oxide based catalysts for the in-situ reactions of methanation and desulfurization in the removal of sour gases from simulated natural gas - Wan Abu Bakar, Wan Azelee (Canadian Center of Science and Education, 2008)
The objective of this novel catalyst development is to achieve both low temperature and high conversion of sour gases of H2S and CO2 present in the natural gas. The results showed that the conversion of H2S to elemental sulfur on all of the potential catalysts was achieved 100 %. However, methanation of CO2 in the presence of H2S yielded 0.7 % CH4 over Fe/ Zn/ Cu/ Ti-Al2O3 catalyst, 1.1 % CH4 over Fe/ Zn/ Cu-Al2O3 catalyst and the highest is 6.1 % CH4 over Pr/ Co/ Ni-Al2O3 catalyst at maximum studied temperature of 300 oC. The catalysts were further characterized by X-rays Photoelectron Spectroscopy and Nitrogen Adsorption analysis. XPS results revealed Ni2+ ion in the NiO and Ni3+ in Ni2O3 species, spinel compound of Co3O4 on the Pr/ Co/ Ni-Al2O3 catalyst. N2 adsorption-desorption analysis illustrated 7.9 % increment of surface area over the spent Pr/ Co/ Ni-Al2O3 catalyst, which assumed to be responsible for the dramatical increased of the methanation activity of this catalyst at the reaction temperature of 300 oC.